Case Study on Memristor-Based Multilevel Memories - Söll, Christopher; Reichenbach, Marc; Röber, Jürgen; Hagelauer, Amelie Marietta; Weigel, Robert; Fey, Dietmar (International Journal of Circuit Theory and Applications, 2018)
In this work, the benefits of memristor-based multilevel memories are described along with their design problems. Starting with measurements of discrete actual devices, a discrete memristor based multilevel memory is developed. It uses a printed circuit board in order to connect eight packaged memristors from Bio Inspired to test a ternary Arithmetic Logic Unit (ALU) on a field programmable gate array (FPGA). These circuits are then integrated in the second proposed memory system based on a 150nm CMOS process that can be equipped with memristors on top of the metal layers. This integrated solution includes proper read-out, erase and write circuits to control real memristors, and 32x32 memristive memory cells. It is compared to a common static random-access memory (SRAM) in terms of area, computation speed and power consumption showing benefits for memory sizes bigger than 70 words. Since yield and device variations are still a big issue in memristor fabrication, methods to counter these problems are also proposed in the end. An actual implementation should offer several trimming solutions to ensure proper functionality of a prototype memory as well as a power-on calibration, until these problems are solved. The development of the presented memories is not only based on different models but also measurements done with real devices.
elib2cris::1512001600,soell2017
Keywords: Memristor; Multi-Level Memory; Memory Interface; Memristive Computing; GRK-1773